The Attitude of Israel's Tradition in Comparison with Tradition of Other Peoples - Weinfeld, M.
comparison with Assyrians, Hittites, etc.; in Talmudic tradition killing a foetus does not involve death penalty, and execution of a pregnant woman is not prohibited; in Hebrew.